Local sub-estimates of solutions to double phase parabolic equations via nonlinear parabolic potentials - Buryachenko, K.O. (Український математичний вісник, 2019)
For parabolic equations with nonstandard growth conditions, we prove local boundedness of weak solutions in terms of nonlinear parabolic potentials of the right-hand side of the equation.